Advertisement call of Scinax littoralis and S. angrensis (Amphibia: Anura: Hylidae), with notes on the reproductive activity of S. littoralis - Garey, Michel V. [UNESP]; Costa, Thais R. N.; de Lima, André M. X.; Toledo, Luís F.; Hartmann, Marília T. (My University, 2012)
Scinax littoralis and S. angrensis are poorly known Atlantic forest endemic species from the Scinax catharinae group, which is known from southern and southeastern Brazil. Herein, we describe the advertisement calls of these two species and compare them to other species within the S. catharinae group. Additionally, we provide information on breeding sites, and calling activity in S. littoralis. Advertisement calls of S. angrensis and S. littoralis are composed of multi-pulsed notes with multiple frequency bands and frequency modulation. Scinax littoralis has a higher minimum and maximum frequency, and lower dominant frequency than S. angrensis, while Scinax littoralis has a longer call. Scinax littoralis appears to be a habitat generalist, occurring from secondary to mature forests, and breeding both in temporary and in permanent ponds. Male S. littoralis were usually observed calling perched on shrub stems, and displayed satellite behavior when the male density was high. © Firenze University Press.
Keywords: Bioacoustics; Breeding activity; Satellite behavior; Treefrog; Vocalization